Pioglitazone enhances brain mitochondrial biogenesis and phase II detoxification capacity in neonatal rats with 6-OHDA-induced unilateral striatal lesions - Vázquez-González, Daniela; Corona, Juan Carlos (Frontiers in Neuroscience, 2023)
The psychostimulant methylphenidate (MPH) is the first-line pharmacological treatment for attentiondeficit/hyperactivity disorder (ADHD), but has numerous adverse side effects. The PPARγ receptor agonist pioglitazone (PIO) is known to improve mitochondrial bioenergetics and antioxidant capacity, both of which may be deficient in ADHD, suggesting utility as an adjunct therapy. Here, we assessed the effects of PIO on ADHD-like symptoms, mitochondrial biogenesis and antioxidant pathways in multiple brain regions of neonate rats with unilateral striatal lesions induced by 6-hydroxydopamine (6-OHDA) as an experimental ADHD model. Unilateral striatal injection of 6-OHDA reduced ipsilateral dopaminergic innervation by 33% and increased locomotor activity. This locomotor hyperactivity was not altered by PIO treatment for 14 days. However, PIO increased the expression of proteins contributing to mitochondrial biogenesis in the striatum, hippocampus, cerebellum and prefrontal cortex of 6-OHDA-lesioned rats. In addition, PIO treatment enhanced the expression of the phase II transcription factor Nrf2 in the striatum, prefrontal cortex and cerebellum. In contrast, no change in the antioxidant enzyme catalase was observed in any of the brain regions analyzed. Thus, PIO may improve mitochondrial biogenesis and phase 2 detoxification in the ADHD brain. Further studies are required to determine if different dose regimens can exert more comprehensive therapeutic effects against ADHD neuropathology and behavior.